2017
DOI: 10.1038/srep44132
|View full text |Cite
|
Sign up to set email alerts
|

Changes in miRNA in the lung and whole blood after whole thorax irradiation in rats

Abstract: We used a rat model of whole thorax x-ray irradiation to profile the microRNA (miRNA) in lung and blood up to 4 weeks after radiation. MiRNA from normal and irradiated Wistar rat lungs and whole blood were analyzed by next-generation sequencing and the changes by radiation were identified by differential deRNA-seq 1, 2, 3 and 4 weeks after irradiation. The average total reads/library was 2,703,137 with a mean of 88% mapping to the rat genome. Detailed profiles of 100 of the most abundant miRNA in rat blood and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 56 publications
(84 reference statements)
1
23
0
Order By: Relevance
“…PDE5-I impacts the enzyme globally, including in the lung where PDE5 expression is prominent (33). To test if its effects on miR expression were organ independent, we examined lungs from normal and PO mice, assaying those known to be highly expressed in lung (34,35). All were confirmed as being reduced in PO+PDE5-I myocardium by qPCR and/or miR-seq, yet none were altered in lungs by PDE5-I under either condition ( Figure 5B and Supplemental Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…PDE5-I impacts the enzyme globally, including in the lung where PDE5 expression is prominent (33). To test if its effects on miR expression were organ independent, we examined lungs from normal and PO mice, assaying those known to be highly expressed in lung (34,35). All were confirmed as being reduced in PO+PDE5-I myocardium by qPCR and/or miR-seq, yet none were altered in lungs by PDE5-I under either condition ( Figure 5B and Supplemental Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Curating microRNAs as radiation markers has been gaining significant traction in recent years 13,[34][35][36] . The small endogenous RNA theoretically modulates up to 30% of the entire human genome and thereby regulates a wide variety of cellular and molecular functions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has indicated that the expression of miR-144-5p, miR-144-3p, miR-142-5p, and miR-19a-3p in whole blood extends the lifespan of rats for 2 weeks after radiation [ 13 ]. However, little is known about the role of miR-144-5p in modifying the radiosensitivity of lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%